PENGGUNAAN NARKOBA DIKALANGAN WANITA DI DESA GANTING KECAMATAN SALO KEBUPATEN KAMPAR - ", Fadli; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The study is done in the village of Ganting Salo district sub-district Kampar. The purpose of this research is to know what are the That such me a housewife drugs and the impacts what happened on households and social environment women using drugs. To obtain data needed in this research, Writer conduct data collection by directly place of research locations and with conducting observations and conducted interviews in depth. Informants in this research were five people. The data collected already dressed in the form of qualitative analysis descriptive. The research there are that intrinsic factor and extrinsic in drug use with girls the village Ganting Salo Sub Kampar, The image of respondents named because the effects of their peers. Then respondents named lina , mega , and ita Family affluence and surrounding environment . Aside from the issue of their peers and family, Economic factors the most powerful affect drug use with girls the village Ganting Salo Sub Kampar by Citra,Evi,Lina,Mega and Ita Namely having persons nearest, The reason for them the family are the nearest because they always associated almost every day due to have a profession and the same job So that economic also had an influence on what they do because these are sourced of economics such as the the education of their children , eat family and others All is because the results of work as drug dealers. This resulted in fifth it was the subject of taking drugs. Advice: to family , should family of more give attention to members of nice family housewives as Wife and housewives as a son. For the government in the effort to reduce drugs abuse non penal on housewife with through social control and attention from the community be given higher priority. To teenagers in the effort to reduce drugs that is teenagers must be more careful in response to various measures of others Coming from outside. The community must more care to the mother of households who had trouble in the economy by a working group mum households more independen, So that their destiny more terperhatikan welfare. So that they do not working to find money hit the road that is not true. Law enforcement should be bold to refuse negotiations of suspects dealers narcotics to manipulate evidence in order to relieve demands to suspect drug dealer. To informants should informants more receptive to her family when having heavy loads And any problem. As small as of any problems can be solved with .Password: the impact of , the causes of and drugs